FROM RADICAL TO MODERATE? A RHETORICAL ANALYSIS OF USTAD FELIX SIAUW - Husna, Ilya; Handayani, Dina Fitria; Azkiya, Hidayati Azkiya (Universitas Negeri Makassar, 2025)
The study aims to examine the rhetorical transformation of Ustaz Felix Siauw’s da'wah in digital media. Using a qualitative method and Aristotle’s rhetorical theory (ethos, logos, pathos), this study analyzes his appearance in a Malaka YouTube podcast. The unit of analysis in this study is the verbal transcript of the podcast episode, which lasts over an hour and is publicly accessible. Data were collected through observation of the podcast video, followed by transcription, and categorization based on Aristotle’s three main rhetorical elements. The findings reveal his strategic use of credibility, logical argumentation, and emotional appeal to reshape his image. While his ideological content remains rooted in Islamic political thought, his delivery has become more dialogical and adaptive. The study concludes that this shift signifies a rhetorical moderation in style, not a fundamental change in ideological orientation.